THE EFFECT OF FINANCIAL LITERACY AND SELF-EFFICACY ON INTEREST IN USING PEER TO PEER LENDING AMONG MILLENNIALS - Lisa Asriyani; Irni Rahmayani Johan (Journal of Child, Family, and Consumer Studies, 2023)
Interest in using peer to peer lending (P2P) is a drive that comes from within a person to make online loans. Along with increasing internet access and device users in Indonesia, P2P service customers also show a significant increase every year. The purpose of this study is to analyze the effect of financial literacy and self-efficacy on interest in using peer to peer lending. This study uses an explanatory design on 234 samples of millennial generation in Jabodetabek selected through purposive sampling technique with online data collection method. Data processing and analysis were conducted using Microsoft Excel 2010 software and IBM Statistical Package for Social Science (SPSS) 22.0. The process of coding, editing, scoring, entering and cleaning data was carried out using the Microsoft Excel 2010 program. The results showed that financial literacy and self-efficacy were in the moderate category, while interest in use was categorized as low. Regression tests show that the number of dependents, types of debt loans, and attitudes towards P2P lending have a significant positive effect on interest in using P2P lending, while financial knowledge has a significant negative effect on interest in using P2P lending. The scope of research is suggested to be spread evenly from various provinces and tribes in Indonesia, so that the results obtained are more accurate and become a reference for the government to improve performance on financial technology lending.